Failure of Anticoagulant Thromboprophylaxis. Issue 2 (February 2015) - Lim, Wendy; Meade, Maureen; Lauzier, Francois; Zarychanski, Ryan; Mehta, Sangeeta; Lamontagne, Francois; Dodek, Peter; McIntyre, Lauralyn; Hall, Richard; Heels-Ansdell, Diane; Fowler, Robert; Pai, Menaka; et al.
<x xml:space="preserve">Abstract</x> Objectives: To identify risk factors for failure of anticoagulant thromboprophylaxis in critically ill patients in the ICU. Design: Multivariable regression analysis of thrombosis predictors from a randomized thromboprophylaxis trial. Setting: Sixty-seven medical-surgical ICUs in six countries. Patients: Three thousand seven hundred forty-six medical-surgical critically ill patients. Interventions: All patients received anticoagulant thromboprophylaxis with low-molecular-weight heparin or unfractionated heparin at standard doses. Measurements and Main Results: Independent predictors for venous thromboembolism, proximal leg deep vein thrombosis, and pulmonary embolism developing during critical illness were assessed. A total of 289 patients (7.7%) developed venous thromboembolism. Predictors of thromboprophylaxis failure as measured by development of venous thromboembolism included a personal or family history of venous thromboembolism (hazard ratio, 1.64; 95% CI, 1.03–2.59; p = 0.04) and body mass index (hazard ratio, 1.18 per 10-point increase; 95% CI, 1.04–1.35; p = 0.01). Increasing body mass index was also a predictor for developing proximal leg deep vein thrombosis (hazard ratio, 1.25; 95% CI, 1.06–1.46; p = 0.007), which occurred in 182 patients (4.9%). Pulmonary embolism occurred in 47 patients (1.3%) and was associated with body mass index (hazard ratio, 1.37; 95% CI, 1.02–1.83; p = 0.035) and vasopressor use (hazard ratio, 1.84; 95% CI, 1.01–3.35; p = 0.046). Low-molecular-weight heparin (in comparison to unfractionated heparin) thromboprophylaxis lowered pulmonary embolism risk (hazard ratio, 0.51; 95% CI, 0.27–0.95; p = 0.034) while statin use in the preceding week lowered the risk of proximal leg deep vein thrombosis (hazard ratio, 0.46; 95% CI, 0.27–0.77; p = 0.004). Conclusions: Failure of standard thromboprophylaxis using low-molecular-weight heparin or unfractionated heparin is more likely in ICU patients with elevated body mass index, those with a personal or family history of venous thromboembolism, and those receiving vasopressors. Alternate management or incremental risk reduction strategies may be needed in such patients.